KONSEP MAGNANIMITY SEBAGAI TUJUAN PENDIDIKAN KARAKTER DALAM FILOSOFI PENDIDIKAN CHARLOTTE MASON - Nugroho, Ellen Christiani (Faculty of Humanities, Diponegoro University, 2012)
It is desirable that education will result not only intelligence, but also noble character in studentsâ€™ personality. This desire should first have its base on strong philosophical answer for the question of why, i.e. why must we educate at all. We then must examine deeply our vision of education which will determine the course of our educational method and action. Charlotte Mason provides us with the concept of magnanimity as the desirable end result of character education. This concept embraces holistic aspects of education: the academic, the practical, the philosophical, and the spiritual. High thinking balanced with lowly living, wide interests on different kinds of subjects, a lifelong-lasting desire to learn are her some criteria of that desirable end result. She insists that educators should hold grand vision and aim as highest as possible, not merely limited by materialistic or utilitarian scheme of success. Education then will become more than a system, but a method, i.e. a flexible attempts to achieve substantially clear educational goal. Keywords: magnanimity, education, Charlotte Mason Â